People centered social innovation: global perspectives on an emerging paradigm - Banerjee, Swati; Carney, Stephen; Hulgård, Lars (Routledge studies in social enterprise & social innovation, 2020)
People Centered Social Innovation: Global perspectives on an Emerging Paradigm attempts to revisit and extend the existing understanding of Social Innovation in practice by focusing upon the lived realities of marginalized groups and communities. The emerging field of people-centered development is placed in dialogue with theory and concepts from the more established field of social innovation to create a new approach; one that adopts a global perspective, engaging with very different experiences of marginality across the global north and south. Theoretically, ‘People Centered Social Innovation: Global Perspectives on an Emerging Paradigm’ draws upon ‘northern’ understandings of change and improvement as well as ‘southern’ theory concerns for epistemological diversity and meaning making. The result is an experiment aimed at reimagining research and practice that seriously needs to center the actor in processes of social transformation.
Keywords: Innovation sociale; Réservé UdeM; Transformations sociales